1976
DOI: 10.1152/ajplegacy.1976.231.4.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonia via prepyriform cortex on regulation of food intake in the rat

Abstract: Studies were made on whether ammonia, which is an obligatory intermediate of amino acid metabolism, depresses the food intake of rats fed a low-casein (basal) diet containing imbalanced amino acid mixtures (imbalanced diets). Bilateral lesions in the prepyriform cortex caused normalization of food intake of rats fed amino acid-imbalanced diets, confirming the work of Leung and Rogers (Am. J. Physiol. 221:929-935, 1971). Unlike normal rats, animals with prepyriform cortical lesions consumed as much of a diet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…1 and 2) inhibits hunger mechanisms and leads to weight loss. An additional more direct link between hyperammonemia and feeding behavior was reported by Noda and Chikamori who observed reductions in food intake after ammonium chloride injections into the prepyriform cortex (35). Thus, hyperammonemia may lead to reductions in food intake by direct or indirect actions on cerebral satiety control centers.…”
Section: Discussionmentioning
confidence: 84%
“…1 and 2) inhibits hunger mechanisms and leads to weight loss. An additional more direct link between hyperammonemia and feeding behavior was reported by Noda and Chikamori who observed reductions in food intake after ammonium chloride injections into the prepyriform cortex (35). Thus, hyperammonemia may lead to reductions in food intake by direct or indirect actions on cerebral satiety control centers.…”
Section: Discussionmentioning
confidence: 84%
“…ROGERS and LEUNG (1973) suggested that the prepyriform cortex and medial amygdala are involved in the response of rats to diets low in, or devoid of, a single essential amino acid, but not those high in leucine or protein. NODA and CHIKAMORI (1976) demonstrated that ammonia acting on the prepyriform cortex may play a role in depressing food intake due to amino acid imbalanced diet.…”
Section: Discussionmentioning
confidence: 99%
“…This sensory role for the APC is based on the following: (a) ablations of the APC by brain lesions that show its essentiality for detection of IAA deficiency [2325] (these lesions were replicated in the rat [26], and in the bird [27]), (b) repletion by injecting nanomole amounts of the limiting IAA into the APC to block the anorectic responses [2830], and (c) electrophysiological measures that show neural activation of the APC in IAA depletion, both in vivo [31] and in vitro [32]. These findings have been reviewed in detail [25, 3335].…”
Section: Protein and Iaa Deficiencymentioning
confidence: 99%